2020
DOI: 10.1111/sum.12650
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sandy soil hydro‐physical properties as function of biochar and biogas slurry amendments

Abstract: Raising a sandy soil's ability to retain more water is an important strategy to manage sandy soils. Combined application of biochar and slurry was hypothesized to be an appropriate strategy for improving soil hydro-physical properties. A two-season field trial was conducted by cultivating peanut (Arachis hypogaea L.) on a sandy soil under permanent overhead sprinkler irrigation. Rice straw biochar at 0, 10, 20 and 30 Mg ha −1 and biogas slurry at 0, 5, 10 and 15 Mg ha −1 were applied. Results indicated that al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Biochar has been found to be effective in alleviating soil loss because of erosion. When combined with NPK fertilizers, biochar was found to be particularly effective in decreasing soil erosion because of runoff (Bashagaluke et al., 2019), owing to improved hydro‐physical properties (Abdo, 2020). Waste walnut wood biochar significantly reduced wind erosion (Pajouhesh et al., 2020).…”
Section: Biochar For Soil Healthmentioning
confidence: 99%
“…Biochar has been found to be effective in alleviating soil loss because of erosion. When combined with NPK fertilizers, biochar was found to be particularly effective in decreasing soil erosion because of runoff (Bashagaluke et al., 2019), owing to improved hydro‐physical properties (Abdo, 2020). Waste walnut wood biochar significantly reduced wind erosion (Pajouhesh et al., 2020).…”
Section: Biochar For Soil Healthmentioning
confidence: 99%
“…As two kinds of widely sourced, safe, and multifunctional organic-waste-derived materials, biochar and biogas slurry can play different roles in soil amendments, and therefore, they were always co-applied in farmland soils to achieve efficient amendment. For example, Abdo [19] co-applied the biochar and BS in sandy soil, and this field research indicated that this combination of 10 and 15 Mg ha −1 biochar and BS can reduce soil bulk and increase the field water capacity. Guo et al [20] investigated the effect of cow dung biochar addition on nutrient leaching of BS-amended acidic yellow soil, and found that the increasing biochar and BS application amount can both enhance the availability and leaching amount of the soil phosphorus and potassium.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have investigated biochar effects on soil hydraulic properties (Abdo, 2020; Liang et al, 2021), there have been varying result, ranging from a decrease to no significant effects (Atkinson, 2018; Jeffery et al, 2015; Wang et al, 2021). It has also been widely shown that soil hydraulic characteristics are greatly affected by soil structure and colloidal properties.…”
Section: Introductionmentioning
confidence: 99%